Crystal Orientations Dependent Polarization Reversal in Ferroelectric PbZr0.2Ti0.8O3 Thin Films for Multilevel Data Storage Applications. Issue 23 (10th November 2021) - Pravarthana, Dhanapal; Wei, Jiafeng; Wang, Baomin; Luo, Fan; Yang, Huali; Guo, Shanshan; Mustafa, Zeeshan; Prellier, Wilfrid; Li, Run‐Wei
Abstract: Deterministic creation of multiple ferroelectric states with variant values of polarization in ferroelectric thin films is promising for multilevel data storage applications. However, the intrinsic bi‐stability of ferroelectric switching makes it challenging to achieve. The deterministic ferroelectric states can be achieved by multistep switching through various means such as controlling domain structure and switching by inducing local disorder, and also by crystal orientations. However, to determine the effect of crystal directions on the stability of multistep polarization reversal requires investigation on different crystal directions. A high‐throughput approach namely combinatorial substrate epitaxy (CSE) is utilized to fabricate La0.7 Sr0.3 MnO3 (LSMO) polycrystalline substrate to grow PbZr0.2 Ti0.8 O3 (PZT) films epitaxially with different crystal directions in a single sample. The polarization reversal area is determined as a function of applied voltage along different < hkl >. From the analysis, it is found that all < hkl > exhibit multilevel polarization states due to multistep switching events. Further the degree of multilevel polarization states shows a sawtooth‐like oscillatory behavior with increase in [111] miscut angle, which is attributed to influence of local disorder on the domain structure. Therefore, the realization of multilevel data storage device based on deterministic polarization reversal can be achieved with appropriate crystal directed thin films. Abstract : A high‐throughput approach is utilized to investigate the effect of crystal directions on multistep polarization reversal in ferroelectric PbZr0.2 Ti0.8 O3 (PZT) thin films. It is found that PZT film with increasing miscut angle from [111] exhibits multistep polarization reversal following a sawtooth‐like oscillatory behavior.